2018
DOI: 10.1002/gea.21699
|View full text |Cite
|
Sign up to set email alerts
|

Calcite alabaster artifacts from Hierapolis in Phrygia, Turkey: Provenance determination using carbon and oxygen stable isotopes

Abstract: Alabastro fiorito or listato, a vividly colored and strongly patterned carbonate stone, is widely diffused in the ancient city of Hierapolis in Phrygia (Turkey) as building material. This stone, also known as Hierapolis alabaster, was extensively quarried in antiquity in the territory near the city. Numerous ancient quarries of the Hierapolis alabaster were documented in previous studies in sites immediately around the city and also about 13 km northwest of Hierapolis, near Gölemezli. Carbon and oxygen stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…The calcite alabaster quarried in the northern side of the Lykos valley, manly close to Hierapolis but also near the modern village of Gölemezli and the ancient city of Tripolis, was available in varieties that are both coloured (listato and fiorito, generally depending on whether the stone is cut along or against the grain) and completely white (ghiaccione). This calcite alabaster is a compact banded and translucent calcium carbonate stone; in geological terms, it is defined banded travertine [43] (p. 2). In particular, listato alabaster is characterized by veining in more or less densely packed bands, both linear and undulating, with a wide range of shades, among which the most frequent are yellow, reddish brown and rusty red, while fiorito has rounded inclusions of the same colours.…”
Section: The Quarrying and Use Of Alabasters In Hierapolis And In The Other City Of The Lykos Valley: First Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The calcite alabaster quarried in the northern side of the Lykos valley, manly close to Hierapolis but also near the modern village of Gölemezli and the ancient city of Tripolis, was available in varieties that are both coloured (listato and fiorito, generally depending on whether the stone is cut along or against the grain) and completely white (ghiaccione). This calcite alabaster is a compact banded and translucent calcium carbonate stone; in geological terms, it is defined banded travertine [43] (p. 2). In particular, listato alabaster is characterized by veining in more or less densely packed bands, both linear and undulating, with a wide range of shades, among which the most frequent are yellow, reddish brown and rusty red, while fiorito has rounded inclusions of the same colours.…”
Section: The Quarrying and Use Of Alabasters In Hierapolis And In The Other City Of The Lykos Valley: First Resultsmentioning
confidence: 99%
“…However, this extraction area seems larger than the Gölemezli quarries, but much smaller than the quarrying areas close to Hierapolis. The archaeometric characterization of the calcite alabasters extracted close to Hierapolis and at Gölemezli, thanks to stable carbon and oxygen isotopes analyses of 55 samples, allowed for the discrimination among them and between these stones and the other calcite alabasters exploited and exported in antiquity from south-western Anatolia, North Africa (Egypt, Tunisia and Algeria) and Italy [40,43]. In particular, it has been demonstrated that the identification of the Hierapolis and Gölemezli alabasters may be remarkably favoured by the fact that it was quarried away from geological deposits, i.e., the banded travertine of fissure-ridges, typical of the specific area, whose genesis process conferred the alabaster a particular stable carbon and oxygen isotope signature.…”
Section: The Quarrying and Use Of Alabasters In Hierapolis And In The Other City Of The Lykos Valley: First Resultsmentioning
confidence: 99%
See 3 more Smart Citations